The Influence of Adaptive Multimedia Learning on Student Motivation and Retention in Online Higher Education - Saifuddin, Hikmah; Firdaus, Rangga (Program Magister Teknologi Pendidikan Universitas Jambi, 2026)
Online higher education continues to face challenges related to low student motivation, knowledge retention, and active participation. This study aimed to analyze the effect of adaptive multimedia learning on student motivation and retention in online higher education using a mixed-methods approach with a sequential explanatory design. The sample consisted of 324 students from four open universities selected through stratified random sampling. Research instruments included an ARCS-based learning motivation questionnaire, a knowledge retention test, and in-depth interview guidelines. Quantitative data were analyzed using ANCOVA, multiple regression, and path analysis, while qualitative data were analyzed thematically. The findings revealed that students in the experimental group using adaptive multimedia achieved significantly higher motivation scores than the control group (4.37 vs. 3.24; F = 47.83; p < 0.001; Cohen’s d = 0.89). Knowledge retention was also higher in the experimental group (78.6%) compared to the control group (54.2%) with F = 52.16, p < 0.001, and Cohen’s d = 0.94. Active participation reached 87.3% in the experimental group, while the control group achieved only 62.1%. Path analysis showed that content personalization, adaptive feedback, and difficulty adjustment explained 61.4% of the variance in learning motivation, while motivation explained 45.9% of the variance in knowledge retention. These findings confirm that adaptive multimedia improves the effectiveness of online learning through more personalized, relevant, and responsive learning experiences and reinforces the integration of the Cognitive Theory of Multimedia Learning and the ARCS model in adaptive online learning.